ANDROGEN INSENSITIVITY SYNDROME WITH METABOLIC SYNDROME: A CHALLENGE IN BALANCING THE HORMONES - Shah, Fatimah Zaherah Mohamed; Awang, Mohd Hazriq; Warman, Nur’Aini Eddy; Zainordin, Nur Aisyah; Mohamad, Aimi Fadilah; Ghani, Rohana Abdul (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Androgen Insensitivity Syndrome (AIS) is an androgen receptor disorder characterised by complete or partial resistance to actions of androgen. Although features of hypogonadism are well-documented, association of AIS with metabolic disorder is not widely recognized. CASE We describe a case of a female who initially presented at 18-years of age for evaluation of primary amenorrhea. She had infantile female genitalia with minimal secondary sexual characteristics. Investigations revealed high testosterone, with absent uterus and ovaries, and a blind vaginal canal. Chromosomal analysis revealed 46XY, clinching the diagnosis of complete androgen insensitivity syndrome (CAIS). She underwent gonadectomy for removal of intraabdominal testes a year later and was started on hormonal replacement therapy (HRT), initially with Tibolone for six-years, resulting in significant and continuous weight gain. Her body mass index (BMI) increased from 32 to 45 kg/m2 in the next few years. Lifestyle modification was unsuccessful, particularly after she developed knee osteoarthritis and reduced mobility. She was given phentermine, with initial weight loss, but with subsequent rebound. During the next few years, she received different types of HRT and developed multiple obesity-related co-morbidities, namely obstructive sleep apnoea requiring continuouspositive-airway-pressure (CPAP), essential hypertension, dyslipidaemia, fatty liver, and was diagnosed to have type 2 diabetes mellitus at 38 years old. Addition of glucagonlike peptide (GLP)-1 receptor-agonist to metformin resulted in initial weight loss, which then plateaued. Her more recent HRT with estradiol/dydrogesterone caused no further weight-gain. However, with a BMI of more than 50 kg/m2, full complement of metabolic syndrome and incapability of weight reduction and maintenance on medical therapy, she was recommended for bariatric surgery. CONCLUSION This case illustrates the association of metabolic syndrome with AIS, which may contribute to the understanding of the role of androgen receptor in metabolic regulation. Recognising this association aids in understanding the spectrum of conditions associated with AIS and may mitigate some complications due to both androgen and insulin resistance.